Penerapan GMP Sebagai Peningkatan Mutu Produk pada UKM Pengolahan Makanan - Hayu Kartika; Meike Elsye Beatrix (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
Good Manufacturing Practice (GMP) in the food industry is a requirement that must be met to produce products that are safe for consumers to consume, where such practices are implemented to prevent and reduce food contamination. Therefore, an understanding of GMP is needed to address the issues faced by SMEs, including the lack of assurance regarding food safety and quality. Issues regarding food safety and quality assurance are crucial for the food industry. Demands for food safety and quality continue to rise along with consumer demand. The purpose of this service is to provide understanding and implementation of GMP in the production department. The method used involves direct visits, discussions, guidance, and implementation of improvements related to GMP application in the production department. The results of the service obtained before this training from 11 participants were 8 SME participants who were unaware or had not heard of GMP. The results of questionnaire measurements regarding performance and expectations of 12 questions posed showed that some questions received higher performance scores compared to expectations, such as questions regarding the relevance of the service materials to community issues and the cohesion of the community service team. For the average results of each performance and expectation question, a performance score of 3.7 out of 4 was obtained for this service activity, and an expectation score of 3.8 out of 4 was obtained. This indicates that participants felt a high level of satisfaction with the performance and expectations of this GMP service activity.